2019
DOI: 10.1002/biof.1573
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin protects liver against aflatoxin B1‐induced hepatotoxicity through upregulating Nrf2/ARE/HO‐1 pathway

Abstract: Dipeptidyl peptidase-4 inhibitor (DPP-4 inhibitor) such as sitagliptin has been presented as antidiabetic drugs and has numerous restorative advantages over different diseases; however, its defensive role against aflatoxin b1 (AFB1) liver toxicity has not been previously examined. Wistar rats (65 weeks, male) were utilized in the investigation. Animals were divided into five different groups (n = 10): control; AFB1; AFB1 + Sita (50); AFB1 + Sita (100); and Sita (100). Sitagliptin significantly (*p ≤ .05, **p ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…AFB 1 sharply downregulated approximately 70% abundances of these two proteins, which might promote AFB 1 -induced oxidative injury in the liver of broilers. These findings are similar to previous reports [39,40]. Intriguingly, dietary supplementation of HD at 500 and 1000 mg/kg mitigated AFB 1 -induced downregulation of NQO1 and HO1 proteins, which may be attributed to reduced oxidative injury in livers induced by AFB 1 .…”
Section: Discussionsupporting
confidence: 91%
“…AFB 1 sharply downregulated approximately 70% abundances of these two proteins, which might promote AFB 1 -induced oxidative injury in the liver of broilers. These findings are similar to previous reports [39,40]. Intriguingly, dietary supplementation of HD at 500 and 1000 mg/kg mitigated AFB 1 -induced downregulation of NQO1 and HO1 proteins, which may be attributed to reduced oxidative injury in livers induced by AFB 1 .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, for rats, acute oral AFB1 (44–663 μg of AFB1 kg −1 of b. w.) led to liver damage, manifesting in inflammatory infiltrate, nuclear vacuolation and necrosis, in line with our results [ 30 ]. Similar results were reported for Cobb broilers, in which AFB1 induced histopathological lesions; grape seed proanthocyanidin extract (250 and 500 mg kg −1 ) + AFB1 (1 mg kg −1 ) mitigated AFB1’s negative effects in rats with sitagliptin activating the Nrf2-ARE-HO-1 signaling pathway to protect liver against AFB1-induced injury, while tea polyphenols protected hepatotoxicity against AFB1-induced injury in rats [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 77%
“…The Keap1/Nrf2/ARE pathway regulates the expression of many antioxidant enzymes and phase II detoxifying enzymes, such as heme oxygenase-1 (HO-1), GR, glutathione peroxidase (GSH-Px), NAD(P)H dehydrogenase, quinone 1 (NQO1), GST, and SOD. AFs downregulated many antioxidants, including SOD, HO-1, NQO1, GSH-Px, catalase (CAT), GST, and GR, in many studies and experimental models (Yener et al, 2009;Alm-Eldeen et al, 2015;Yang et al, 2016;Vipin et al, 2017;Muhammad et al, 2018a;Muhammad et al, 2018b;Ji et al, 2020). However, one study found that AFs upregulated the expression of Nrf2 (Liu and Wang, 2016).…”
Section: The Dual Role Of Afs In the Regulation Of Autophagymentioning
confidence: 99%